(untitled) (Mugda Medical College Journal, 2025)
Cardiovascular diseases (CVDs) remain a leading global cause of death, accounting for approximately 17.5 million deaths annually, with over 75% occurring in low- and middle income countries (LMICs). A cross-sectional, observational study was conducted between January and July of 2017, to determine knowledge on risk factors and warning signs of cardiovascular diseases among hospitalized patients with acute coronary syndrome (ACS). A total of 192 patients with acute coronary syndrome admitted in the Department of Cardiology, Bangladesh Medical University (BMU), Dhaka, Bangladesh, were enrolled in the study, as per inclusion and exclusion criteria. Data was collected using a semi-structured questionnaire. Face-to-face interview was done for data collection. The majority of patients were in the 40–59 years age-group (65.6%). Male-female ratio was 1.8:1. A statistically significant correlation was found between their level of knowledge and educational status (p<0.001). Patients hailing from urban areas showed a comparatively higher level of expertise. Patients with hypertension have greater knowledge than those without hypertension (p<0.001). Patients with diabetes mellitus and dyslipidemia also showed similar results (p<0.001). However, there was notable gap in knowledge regarding CVD, their risk factors, and warning symptoms. Our study showed that ACS patients have a comparatively poor level of awareness of ACS risk factors and warning indicators. Mugda Med Coll J. 2025; 8(2): 125-132